PENGARUH MODEL THINK-TALK-WRITE TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VI (STUDI QUASI EKSPERIMEN DI UPTD SDN 8 BARRU) - Shadiq, Andi Hasibah; Sulfasyah; Haslinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Think-Talk-Write (TTW) learning model on the ability to write descriptive texts of sixth-grade students of UPTD SDN 8 Barru. This study uses a quantitative approach with a quasi-experimental design of the Non-Equivalent Control Group Design type. The research sample consisted of 20 students selected using purposive sampling due to the limited number of classes at the research location. Data collection techniques were carried out through writing tests (pretest and posttest) assessed with a standard rubric. Data were analyzed using descriptive statistics as well as Paired Sample t-test and Independent Sample t-test. The results showed that the average posttest score of the experimental class (90.4) was significantly higher than the control class (81.5) with a significance value of 0.000 <0.05. It was concluded that the TTW model had a significant effect on improving students' writing abilities because it facilitated cognitive processes gradually through the stages of thinking, discussing, and writing. The limited number of samples showed that the results of this study were contextual.